PENGGUNAAN OBAT RASIONAL BERDASARKAN INDIKATOR WORLD HEALTH ORGANIZATION (WHO) DI PUSKESMAS PADANG PASIR KOTA PADANG - Pusva Sandra Dewi; Eka Yuni Nur Jannah (Journal of Innovation Research and Knowledge, 2025)
Drug is one of the important factors in health services. The World Health Organization (WHO) estimates that around 50% of all drugs use inappropriately in its prescribing, preparation and sale. The other 50% are not used properly by patients. This study aims to assess the rationality of rational use of drugs in Padang Pasir Public Health Center according to WHO indicators using a cross-sectional study design with a random sampling method. The result of the research that have been done showed the rational use of drugs in Padang Pasir Public Health Center based on some parameters still do not meet the standards set by WHO. For prescription indicators, especially for the average parameter, drug per-patient 2.80 (2,6); percentage of antibiotic prescribing in patients with non-specific diarrhea 0% (20%); percentage of prescription drugs from the National List of Essential Medicines 88% (100%); In patient care indicators, especially for the average parameters consultation time is 3 minutes (10 minutes); percentage of patients who understood the drug regimen 77% (100%); Meanwhile, the facility indicator, especially the average parameter, the percentage of essential drug availability is 90.62% (100%). However, there are several parameters that have met the standards set by WHO, in the prescription parameters, especially for the percentage parameter of prescription antibiotics for non pneumonia, 100% (100%). In patient care indicators, especially for percentage parameters of drugs that are actually prepared is 100% (100%); percentage of drugs with sufficient labeling is 100% (100%). On the facility indicator, especially for the parameters, there is DOEN / Formulary at Padang Pasir Public Health Center. It can be concluded that the rational use of drugs based on World Health Organization indicators at Padang Pasir Public Health Center has not met the criteria.